Frontotemporal Lobe Degeneration as Origin of Scans Without Evidence of Dopaminergic Deficit - Menéndez-González, Manuel; Álvarez-Avellón, Tania; Salas-Pacheco, José M.; de Celis-Alonso, Benito; Wyman-Chick, Kathryn A.; Arias-Carrión, Oscar (Frontiers in Neurology, 2018)
The term scans without evidence of dopaminergic deficit (SWEDD) can be associated to any patient diagnosed at first with Parkinson´s disease but with a negative dopamine transporter-single, photon emission computed tomography (DaTSPECT), which does not confirm the presynaptic-dopaminergic deficiency. Therefore, an alternative diagnosis should be sought to support parkinsonism as a clinical diagnosis. Parkinsonism is a well-known manifestation of frontotemporal lobar degeneration (FTLD), particularly frequent in those with positive DaTSPECT. Here we reinforce previous observations that parkinsonism can be present in FTLD patients with negative DaTSPECT and therefore FTLD may account for a percentage of patients with SWEDD. We gather the clinical observations supporting this hypothesis and describe a case report illustrating this idea. Studies suggest the result of DaTSPECT in FTLD may depend on the neuropathology and clinical subtype. However, most studies do not provide a clinical description of the clinical subtype or pathological features making the association between subtypes of FTLD and DaTSPECT results impossible at the moment. Further studies correlating clinical, neuropsychological, neuroimaging, genetic, and pathology findings are needed to better understand parkinsonism in FTLD.